2012
DOI: 10.1039/c2ra01239a
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks and related materials for hydrogen purification: Interplay of pore size and pore wall polarity

Abstract: The separation of hydrogen from other weakly adsorbing gases is a topic of high industrial relevance. Microporous materials, such as zeolites, metal-organic frameworks (MOFs), and nanoporous molecular crystals, hold much promise as adsorbent materials for adsorption-based hydrogen separation units. However, most experimental and theoretical studies that have been reported so far have focused on relatively few gas mixtures (mainly CO 2 /H 2 and CH 4 /H 2 ). In this work, the suitability of five materials (zeoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 75 publications
0
27
0
Order By: Relevance
“…[49,50] For the guest species, parameters tested in previous work were employed. [26,27] Simulation snapshots extracted from the Monte Carlo simulations were then optimised using the same force field parameters.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…[49,50] For the guest species, parameters tested in previous work were employed. [26,27] Simulation snapshots extracted from the Monte Carlo simulations were then optimised using the same force field parameters.…”
Section: Computational Detailsmentioning
confidence: 99%
“…towards C 2 H 2 /CO 2 , CO/H 2 , and O 2 /H 2 mixtures, and analysed the spatial evolution of the interaction energy in the channels for these guest molecules. [26,27] Monte Carlo simulations of adsorption were also employed to aid the aforementenioned experimental investigation of Xe/Kr separation. [19] Electronic structure methods, such as density-functional theory (DFT), can be employed to study the interaction of porous materials with adsorbed guest molecules from first principles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…USTA-50 [31] has high C 2 H 2 /CH 4 and C 2 H 2 /CO 2 separation selectivity of 68 and 13.3 respectively, but the uptake amount of acetylene is only 91 cm 3 g -1 at 296 K and 1 atm. Recently optimizing pore spaces has been known as another efficient method to confine gas molecules in frameworks and increase adsorption selectivity [32][33][34][35]. Lin and co-workers [36] have demonstrated that by introducing methyl groups into ligand to create smaller pores can enhance the isosteric heat of adsorption and improve H 2 adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10][11] For all types of membranes, their permeances are inversely proportional to their thickness; as a result, a one-atom thin membrane is a promising candidate for separation processes. 6,[8][9][10][11] For all types of membranes, their permeances are inversely proportional to their thickness; as a result, a one-atom thin membrane is a promising candidate for separation processes.…”
mentioning
confidence: 99%